Deteksi Molekuler Tilapia Lake Virus (TiLV) pada Ikan Nila (Oreochromis niloticus) di Provinsi Kalimantan Timur, Indonesia - Fitri Noerhidayanti; Fatmy Yaumil Akhir Jafar; Fitriyana Fitriyana (Inovasi Kesehatan Global, 2026)
Tilapia Lake Virus (TiLV) is an RNA pathogen that causes high mortality rates in tilapia (Oreochromis niloticus), posing a major threat to global aquaculture. This study aimed to detect the presence of TiLV in tilapia populations in East Kalimantan Province, Indonesia, using the Polymerase Chain Reaction (PCR) method. A total of 60 tilapia samples were collected from three main aquaculture areas: Kutai Kartanegara, Samarinda, and Penajam Paser Utara. Molecular analysis revealed that one sample from Penajam Paser Utara was positive for TiLV, with an overall prevalence of 5%, while all samples from other sites tested negative. This finding indicates that TiLV has been molecularly detected in East Kalimantan, albeit at a low prevalence. The overall prevalence of TiLV infection in East Kalimantan was 1.67%. The results provide important baseline data for strengthening disease surveillance, biosecurity implementation, and the development of preventive strategies in tilapia aquaculture systems in Indonesia.